Mechanism of dye solubilization and de-aggregation by urea. (September 2021) - Perry, James M.; Nagai Kanasaki, Yu; Karadakov, Peter B.; Shimizu, Seishi
Abstract: Urea is an effective solubilizer for dyes with low aqueous solubility. To establish, at a molecular level, the reason behind the action of urea as an effective solubilizer, we employ a rigorous statistical thermodynamics approach based on the Kirkwood-Buff theory of solutions. We show that (i) contrary to the classical hypothesis on "water structure breaking", the effect of urea on dye hydration makes a minor contribution to solubilization; (ii) the driving force of solubilization is the accumulation of urea around hydrophobic dye molecules. Highlights: Why urea is an effective dye solubilizer was clarified using statistical thermodynamics. The effect of urea on dye hydration makes a minor contribution to solubilization. The accumulation of urea around hydrophobic dye molecules drives solubilization.